Carbon Footprint Reduction a Critical Study of Rubber Production in Small and Medium Scale Enterprises in Sri Lanka - Dayaratne, Sampath P.; Gunawardana, Kennedy D. (My University, 2015)
In response to the winds of change world over, as a result of rapid advance in science and technology, it has strengthened the Small and Medium Scale Enterprises (SMEs) to exert themselves as engines of their economy in the sphere of production as a whole economy as well as increase of production and competition in the market. This situation is augmented as a result of consumer demand. Its impact is such that we discern a rapid increase of population, urbanization, social mobility and transition with vigorous competition. Looking at opportunities to maximize production to satisfy customer needs, SMEs do not consider the factors that affect environment during manufacturing process, selling and distribution and consumption stages. Considering the magnitude of the excessive toxic effect on the biosphere and in order to protect the natural environment for the sustenance and conservation of organisms, it is imperative for all the parties concerned to take up responsibility to include carbon footprint mitigating measures during industrial processes. Available literature revealed that different types of systems have been set up to minimize carbon footprint by the industry at both national and international levels, but still there are issues on identifying carbon footprint usage and emission levels along with implementation systems/methodologies introduced. Researchers identified energy consumption being largely associated at the rubber mill and emissions are extraordinarily connected to productivity of kW/H of energy consumption. In order to carry out research goal barriers in implementing energy-efficient carbon footprint minimization measures, responses to one hundred questionnaires were collected from rubber product manufacturing SMEs registered under the Ministry of Industry and Commerce, Sri Lanka. Twenty five unstructured interviews were conducted with relevant professionals in order to ascertain their opinion. There are vital findings in this research d mainly the correlation of factors affecting relationship on minimizing energy efficient carbon footprint effects which will phase-in obliging emphasis on policy makers to rethink their planning. This was proved by using the fishbone model. Major barriers were identified by using content analysis of respondents. In order to identify the CO2 emission level, the researcher examined the calculation model developed from the results to quantify carbon emission level from the three rubber-band manufacturing factories that were selected as case study domains. Case-studies revealed the overall emissions from the production of rubber band amounting to 1.16, 1.53 and 1.23 ton CO2-eq/ton product respectively. These findings could be directly benefited by any country where rubber production is being put into practice; in order to identify factors that would minimize global warming potentials of rubber manufacturing SMEs, by the application of cleaner manufacturing model to achieve sustainable production.
Keywords: Energy-efficient carbon footprint minimizing; Global warming potentials; Small and medium scale enterprises; Sri Lankan rubber industry